The transition of adolescents with juvenile idiopathic arthritis or epilepsy from paediatric health-care services to adult health-care services: A scoping review of the literature and a synthesis of the evidence. (September 2018) - Burke, Lauren; Kirkham, Jamie; Arnott, Janine; Gray, Victoria; Peak, Matthew; Beresford, Michael W
Young people with long-term health conditions (LTCs) can face challenges when making the transition to adult health services. This paper sought to identify studies that assess and explore transitional care for young people with LTCs. Two conditions were used as exemplars: juvenile idiopathic arthritis (JIA) and epilepsy. A scoping review of the literature was conducted by using search terms to search for papers in English between 2001 and 2016 concerning transitional care on four databases. Qualitative papers were reviewed and synthesized using thematic analysis. Quantitative papers using health outcomes were also synthesized. Twenty-eight papers were selected for review. Despite the wealth of literature concerning aspects of transitional care that are key to a successful transition for young people with JIA or epilepsy, there is a paucity of outcomes that define 'successful' transition and consequently a lack of reliable research evaluating the effectiveness of transitional care interventions to support young people moving to adult health services.